ADMISSIBILITY IN $\sum_n^0$-ENUMERATIONS - Soskova, Alexandra; Soskov, Ivan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1998)
In the paper we introduce the notion of $\sum_n^0 partial enumeration$ of an abstract structure $\mathfrak{A}$. Given a $k ≤ n$, we obtain a characterization of the subsets of $\mathfrak{A}$ possessing $\sum_k^0$ pullbacks in all $\sum_n^0$ partial enumerations of $\mathfrak{A}$.